Effect of Tea Dregs Form and Different Fermentation Process on the Nutrient, Tannin, Saponin, flavonoid content and Antioxidant Activity - Tugiyanti, Elly; Susanti, Emmy; Sulistyawan, Ibnu Hari (Pakistan Journal of Nutrition, 2018)
Background and Objective: The production of tea dregs increases every year. Tea dregs contain high levels of nutrients, bioactive compounds that are antioxidants and some antinutrients. The aim of the study was to assess the effect of fermentation on levels of nutrients, tannins, saponin, flavonoids and antioxidant activity of various forms of tea dregs. Materials and Methods: The present study used experimental methods and a completely randomized design. The treatment consisted of fermentation (F) comprising F0: Unfermented, F1: Fermentation using EM-4 and F2: Fermentation using Trichoderma viride. The fermented material was in three forms namely tea dreg-shaped leaf, granules and powders. Each treatment was replicated 4 times. The variables measured were moisture, ash, protein, fat, crude fiber, metabolizable energy, tannins, saponins, flavonoids and antioxidant activity. Results: The fermentation using EM-4 and Trichoderma viride had no significant effect (p>0.05) on the ash content, fat, saponin and flavonoids. However, it had a significant effect (p